PENGEMBANGAN LITERASI WAJAH DAN KARAKTER KOTA DI INDONESIA KEPADA ANAK-ANAK PANTI ASUHAN ISTANA YATIM AL-JUFRI DI KAMPUNG TUA PATAM LESTARI KELURAHAN PATAM LESTARI KECAMATAN SEKUPANG KOTA BATAM - Fahin Winukaryahan; Farid Ahmad Marzuki; Viven Martan; Yuanita FD Sidabutar; Malahayati Rusli Bintang; Raymond Raymond (Jurnal Abdimas Bina Bangsa, 2023)
Developing literacy on the face and character of cities in Indonesia for the children of the "Al-Jufri Yatim Palace" orphanage in Kampung Tua Patam Lestari, Patam Lestari Village, Sekupang District, Batam City is an international community service activity involving Batam University and Mara Cawangan Johor Technology University , Malaysia. Literacy regarding the face and character of cities in Indonesia is not only limited to the ability to read and write for children in orphanages, but is more about the formation of values ​​and norms as well as positive personalities and of course this activity is becoming increasingly important, especially in the environment for children in orphanages. Community service activities are one form of implementation of the Tridharma of higher education, namely Education, Research and Community Service. Developing facial and character literacy in orphanages is a necessity so that children in orphanages can grow into individuals who are competitive and have noble character